GROWTH PERFORMANCE, BODY WEIGHT PREDICTION AND HAEMOTOLOGICAL INDICES OF RABBITS FED RUMEN LIQUOR FERMENTED SUGARCANE SCRAPPING MEAL - Abdullahi, Hudu Ramalan; Dogara, Muhammad Umar; Itodo, Joy Iyojo; Musa, Muhammad Makama (FUDMA JOURNAL OF SCIENCES, 2024)
The study aimed to assess the impact of incorporating rumen liquor sugar cane scrapping meal (RLFSCSM) into rabbit diets on growth performance, body weight and haemotological indices. A total of 24 mixed breed grower rabbits of similar live weight (700 – 832g) were used and subjected to a Completely Randomized Designed (CRD) with 4 treatments, 3 replicate having 2 rabbits each. The rabbit diets were formulated to replace maize at different percentages 0, 10, 20 and 30% representing T1, T2, T3, and T4 respectively. Feeding and other routine management practices were strictly adhered to according to standard practices throughout the experimental period. The results showed a p
Keywords: Body weight; Growth; Haematology; Prediction; Rabbits